2012
DOI: 10.1007/s10340-012-0419-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, phytotoxic and antifungal activities of Pinus pinea essential oil

Abstract: The chemical composition of essential oils isolated by hydrodistillation from the aerial parts of Tunisian Pinus pinea Linn. was analyzed by GC and GC/MS. Sixty-six compounds were identified, representing 98.5% of total oil, which was found to be rich in monoterpene hydrocarbons (73.1%) particularly limonene (54.1%), a-pinene (7.7%), and b-pinene (3.4%). The yield and the physico-chemical properties were determined. Results of the antifungal activity study by in vitro contact assay showed that P. pinea oil sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 45 publications
3
39
0
1
Order By: Relevance
“…(Table 3) According to Pagula and Baeckström (2006) the main fraction of the essential oils from pine species is monoterpene hydrocarbons (α-pinene, camphene, β-pinene, δ-3-carene, β-myrcene, limonene and β-phellandrene), which is in agreement with published results. Researches with Pinus species show that the main components of the oils are monoterpenes, mainly the hydrocarbon type, composing 60-70% of the oil, followed by oxygenated monoterpenes, sesquiterpenes oxygenated and hydrocarbons (Amri et al 2012;Stevanovic et al 2005;Petrakis et al 2001). Oxygenated monoterpenes were also detected (1.23% in 2011 and 2.83% in 2012) in P. taeda.…”
Section: Chemical Composition Of the Essential Oilmentioning
confidence: 96%
See 1 more Smart Citation
“…(Table 3) According to Pagula and Baeckström (2006) the main fraction of the essential oils from pine species is monoterpene hydrocarbons (α-pinene, camphene, β-pinene, δ-3-carene, β-myrcene, limonene and β-phellandrene), which is in agreement with published results. Researches with Pinus species show that the main components of the oils are monoterpenes, mainly the hydrocarbon type, composing 60-70% of the oil, followed by oxygenated monoterpenes, sesquiterpenes oxygenated and hydrocarbons (Amri et al 2012;Stevanovic et al 2005;Petrakis et al 2001). Oxygenated monoterpenes were also detected (1.23% in 2011 and 2.83% in 2012) in P. taeda.…”
Section: Chemical Composition Of the Essential Oilmentioning
confidence: 96%
“…However, further studies are required to determine the applicability, cost, safety and toxicity of these bioproducts. The composition of the essential oil of P. halepensis (Dob et al 2005) and P. pinea (Amri et al 2012) showed β-pinene (0.2 and 3.4%), α-pinene (1.2 and 7.7%) and β-myrcene (3.1 and 2.7%), respectively. Only 0.36% of β-phellandrene was detected in P. pinea and not detected in P. halepensis, whereas tricyclene was found in both species in traces.…”
Section: Chemical Composition Of the Essential Oilmentioning
confidence: 99%
“…It also has smaller cones that are only 1.5 to 2.5 cm long (Krüssmann, 1985). The present study is the continuation of our previous studies on the possible herbicidal and antifungal activity of essential oils from species belonging to the Pinaceae and Cupressaceae families (Amri et al, 2011a;2011b;2012a;2012b). The first aim of this study was to determine the chemical composition of Pinus pinaster and Cupressus sempervirens var.…”
Section: Introductionmentioning
confidence: 93%
“…Therefore, screening plant essential oils and plant extracts for their biological activity could lead to the discovery of new pest control agents (Isman, 2000;Amri et al, 2012a;2012b). In the literature, several essential oils have shown herbicidal and antifungal activities (Amri et al, 2011a;2011b;2012a;2012b). Furthermore, activities of their individual compounds have been shown (De Martino et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation